The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s0102-67202010000400012
|View full text |Cite
|
Sign up to set email alerts
|

Alterações metabólicas e digestivas no pós-operatório de cirurgia bariátrica

Abstract: -Background -Changes in digestion and nutrients losses are relevant aspects in weight reduction and maintenance of the nutritional status of patients undergoing gastroplasty, but few studies are available in the literature. Aim -To study the systemic changes arising from the reduction in weight over time after surgery. 28,93 and 35,89). The percentage of weight reduction at this stage was 36,31% (p>0,001), one patient had weight gain, in three (6,8%) patients the albumin level was reduced and nine had anemia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
(2 reference statements)
0
6
0
1
Order By: Relevance
“…Hypertension was the most frequent comorbidity, followed by osteoarticular disorders. Brazilian studies with similar populations also found a predominance of young females with class III obesity and comorbidities, especially hypertension (8)(9) . It should be highlighted that, in the present study, 85 (59.4%) of patients had a BMI above 40Kg/m², with high levels of morbid obesity.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Hypertension was the most frequent comorbidity, followed by osteoarticular disorders. Brazilian studies with similar populations also found a predominance of young females with class III obesity and comorbidities, especially hypertension (8)(9) . It should be highlighted that, in the present study, 85 (59.4%) of patients had a BMI above 40Kg/m², with high levels of morbid obesity.…”
Section: Discussionmentioning
confidence: 81%
“…However, studies on nursing care to bariatric surgery patients remain little explored in our institution, since this surgical procedure is relatively recent. In addition, few publications have addressed this topic in the field of nursing (8)(9) , which reveals that there is a knowledge gap on NDs and appropriate care to these patients. Hence, the leading question of the present study was: who are the patients undergoing bariatric surgery and which NDs and nursing care are established in clinical practice?…”
Section: Introductionmentioning
confidence: 99%
“…Although invasive, it has achieved satisfactory results, leading to the reduction of more than 50% of the overweight or 30 to 40% of the initial weight. It aims the reduction of hunger signals and increased satiety, thus, producing a controlled state of undernutrition 10 , 17 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the successful weight loss and improvement of obesity-related comorbidities, the onset of postoperative food intolerances and clinical manifestations are quite common. They are caused by many factors, such as changes in the gastrointestinal system and the slow adaptation of the body to all the changes made by surgery 8 . Intolerances may appear at any time.…”
Section: Introductionmentioning
confidence: 99%